ISSUE ON THE HISTORY OF THE LATINAMERICAN EDUCATION. THIS ISSUE HAS BEEN GATHERING AND LEADING THE HISTORIC-EDUCATIONAL RESEARCH IN LATIN-AMERICA. - Soto Arango, Diana Elvira (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2012)
The Latino American Education History Journal is the first and unique in its gender. It has ten years as a communication medium of two academia issues. ¨The History of Latin-American Education¨ and the PHD on Science of Education that belongs to RUDECOLOMBIA. As an information medium of the research groups that are in the previous program mentioned. This scholarly journal has keep on good position by the researchers´ academic support. It has presented an academic and researching impact for being a medium of consulting referenced. It is catalogued in international indexes and is edited on paper and in the RUDECOLOMBIA webpage.This work established a balance from this publishing of the scholarly journal researchers and the archive source of the Sciences of Education PHD program.